Vilém Mathesius a Pražský lingvistický kroužek - Hyhlíková, Věra (Univerzita Pardubice, 2005)
The main aim of this article is to present the well - know Czech linguist Vilém Mathesius, who created the theory of the actual articulation of the sentence and who was born in Pardubice. The article also describes the history of the Prague Linguistic Circle founded in 1926. It was a group of linguists directed by V. Mathesius. They first discussed the problem of phonology, syntax, the notion of structure of language is determinated by function. The Prague Linguistic School has contributed to the world's linguistics of the 20th century significantly.
Keywords: Mathesius,Vilém; lingvistika; větné členění